Grape seed extracts inhibit dentin matrix degradation by MMP-3 - Khaddam, Mayssam; Salmon, Benjamin; Le Denmat, Dominique; Tjaderhane, Leo; Menashi, Suzanne; Chaussain, Catherine; Rochefort, Gaël Y.; Boukpessi, Tchilalo (Frontiers in Physiology, 2014)
Since MMPs have been suggested to contribute to dentin caries progression, the hypothesis that MMP inhibition would affect the progression of dentin caries is clinically relevant. Grape seed extracts (GSE) have been previously reported to be natural inhibitors of MMPs. Objective: To evaluate the capacity of a GSE mouthrinse to prevent the degradation of demineralized dentin matrix by MMP-3 (stromelysin-1). Material and methods: Standardized blocks of dentin obtained from sound permanent teeth extracted for orthodontic reasons were demineralized with EDTA and pretreated either with (A) GSE (0.2 % w/v), (B) amine fluoride (20 % w/v), (C) a mouthrinse which contains both, (D) placebo, (E) sodium fluoride (0.15 mg.ml-1), (F) PBS, (G) Chlorhexidine digluconate (CHX), or (H) zinc chloride (ZnCl2). The dentin blocks were then incubated with activated recombinant MMP-3. The supernatants were analyzed by Western Blot for several dentin matrix proteins known to be MMP-3 substrate. In parallel, scanning electron microscopy (SEM) was performed on resin replica of the dentin blocks. Results: Western blot analysis of the supernatants revealed that MMP-3 released from the dentin matrix small proteoglycans (decorin and biglycan) and dentin sialoprotein in the amine fluoride, sodium fluoride, PBS and placebo pretreated groups, but not in the GSE and mouthrinse pretreated groups. SEM examination of resin replica showed that the mouthrinse and its active components not only had an anti-MMP action but also modified the dentin surface accessibility. Conclusion: This study shows that GSE either alone or combined with amine fluoride as in the evaluated mouthrinse limits dentin matrix degradation. This association may be promising to prevent the progression of caries within dentin. However, the procedure should be adapted to clinically relevant durations.